2019
DOI: 10.1038/s41541-019-0124-6
|View full text |Cite|
|
Sign up to set email alerts
|

Age-associated changes in the impact of sex steroids on influenza vaccine responses in males and females

Abstract: Vaccine-induced immunity declines with age, which may differ between males and females. Using human sera collected before and 21 days after receipt of the monovalent A/Cal/09 H1N1 vaccine, we evaluated cytokine and antibody responses in adult (18–45 years) and aged (65+ years) individuals. After vaccination, adult females developed greater IL-6 and antibody responses than either adult males or aged females, with female antibody responses being positively associated with concentrations of estradiol. To test whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
194
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(203 citation statements)
references
References 49 publications
8
194
0
1
Order By: Relevance
“…In comparison, the aggregated results of four studies of adults reported only 2 out of 263 individuals who had neutralizing activity >1:10,000 at 2-5 weeks post symptom onset using lentiviral pseudotype assays similar to our own 10,[31][32][33] . Our sample size is too small to draw conclusions about neutralizing immunity in children versus adults, but this is an interesting area for further study, given that children develop stronger or quicker neutralizing responses to some other viruses [34][35][36][37][38] .…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, the aggregated results of four studies of adults reported only 2 out of 263 individuals who had neutralizing activity >1:10,000 at 2-5 weeks post symptom onset using lentiviral pseudotype assays similar to our own 10,[31][32][33] . Our sample size is too small to draw conclusions about neutralizing immunity in children versus adults, but this is an interesting area for further study, given that children develop stronger or quicker neutralizing responses to some other viruses [34][35][36][37][38] .…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 21, 2020. ; https://doi.org/10.1101/2020.08.18.20177303 doi: medRxiv preprint of sex steroids 52,53 . Whether and to what extent this contributes to gender differences seen in clinical outcomes of COVID-19 54 remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The Toll-like receptor 7 gene (Tlr7) is encoded on the X chromosome and is expressed at a higher level by B cells from vaccinated female mice than by B cells from vaccinated male mice, which is associated with reduced DNA methylation in the Tlr7 promoter region in female mice 41 . Data from humans and mice further show that the female bias of antibody responses to influenza vaccination is associated with circulating oestradiol levels, such that greater concentrations of oestradiol result in greater production of antibody to the vaccine antigen 42 . Taken together, both the expression of X-linked genes and increased levels of oestradiol are associated with improved vaccine-induced immunity in females.…”
Section: Slkmentioning
confidence: 99%